2010
DOI: 10.1111/j.1469-0691.2009.03073.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antibodies by Staphylococcus aureus nasal colonization in young children

Abstract: In order to develop novel antistaphylococcal strategies, understanding the determinants of carriage and how humans respond to Staphylococcus aureus exposure is essential. Here, the primary S. aureus-specific humoral immune response and its association with nasal colonization was studied in young children. Sera from 57 colonized or non-colonized children, serially collected at birth and at 6, 14 and 24 months, were analysed for IgG, IgA and IgM binding to 19 staphylococcal proteins, using flow cytometry-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 28 publications
3
55
1
Order By: Relevance
“…HIV-infected patients with a CD4 ϩ T-cell count of Յ200/l have an increased prevalence of persistent colonization (10). In addition, colonized children have significantly higher levels of IgA and IgG against S. aureus proteins than do noncolonized children (11). Despite the evidence provided by these studies, the specific immunological mechanisms for clearance of S. aureus nasal carriage are undefined.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…HIV-infected patients with a CD4 ϩ T-cell count of Յ200/l have an increased prevalence of persistent colonization (10). In addition, colonized children have significantly higher levels of IgA and IgG against S. aureus proteins than do noncolonized children (11). Despite the evidence provided by these studies, the specific immunological mechanisms for clearance of S. aureus nasal carriage are undefined.…”
mentioning
confidence: 56%
“…Previous studies have shown a potential role for antibody-mediated immunity in clearance. IgA and IgG antibodies have been shown to increase in nasally colonized children (11). Additionally, antistaphylococcal antibody levels are higher in persistent carriers than in noncarriers (18).…”
Section: Discussionmentioning
confidence: 97%
“…The Wilcoxon signed rank tests and Mann-Whitney U tests were used for the same type of analyses described previously (34).…”
Section: Methodsmentioning
confidence: 99%
“…Observations of parent-child interaction and behaviour, such as executive function, heart rate variability, infant-parent attachment, moral development, and compliance with mother and child have been performed at the ages of 14, 36 and 48 months and with father and child at the age of 48 months [240,241]. Biological materials have been collected, including bacterial colonization measured by nasal-and nasopharyngeal swabs at the ages of 1.5, 6, 14 and 24 months, cortisol day rhythm measured by repeated salivary samples at the age of 14 months and, if parents give consent, blood samples at the ages of 6, 14 and 24 months [242][243][244][245][246][247][248][249][250][251].…”
Section: Questionnairesmentioning
confidence: 99%